A Simple Feedback Controller to Reduce Angular Momentum in ZMP-Based Gaits. (6th February 2013) - Alcaraz-Jiménez, Juan José; Herrero-Pérez, David; Martínez-Barberá, Humberto
The Zero Moment Point (ZMP) stability criterion has been broadly employed for walking pattern generation in legged robots. However, ZMP-based approaches usually ignore the presence of angular momentum in the system. This hinders the performance of the gait, especially against disturbances. In this work we propose an angular momentum controller that can be integrated into standard ZMP-based gaits. The experiments on a real Nao robot demonstrate that the use of the proposed angular momentum controller improves the stability of a walking pattern generator based on the preview control of the ZMP.